Causas y efectos de la pandemia en la variación de los ingresos y egresos de la Empresa Obrecit en el periodo 2020 - Ayala Mejía, Sandy Lizbeth (2022)
This document aims to study the causes and effects of the pandemic on the variation in income and expenses of the Obrecit Company in the 2020 period, applying a simple methodology that can demonstrate the economic, financial and administrative crisis in the 2020 period, not only because of the health emergency but also because of ill-advised management decisions.